Some Problems of the Realization of Marital Relation with Foreigners - S. S. Myrza; I. A. Serednytska (Law and Safety)
Given that the right to marry is an inalienable right of everyone, guaranteed by international law and national legislation of different world countries, it is accordingly forbidden to interfere with the lawful marriage. At the same time, the marriage procedure in different countries has its own characteristics, which depend on such factors as culture, religion, features of the legal system, etc. The influence of these factors on the marriage with a foreign element and some problems that may arise during its conclusion were taken into account while writing this scientific article. Thus, since the current legislation and the legal system of different countries may significantly vary, there may be some problems in the implementation of marital relations with foreigners, which require more detailed study.